Epidemiology and characteristics of hand burns: a 12-year retrospective analysis at a University Hospital - Laurin Schöne; Jolanta Klukowska-Rötzler; Aristomenis K. Exadaktylos; Radu Olariu; Esther Vögelin; Esin Rothenfluh (Burns Open)
The purpose of this study was to assess epidemiological features and injury characteristics of hand burn injuries based on a retrospective data collection from 2012 to 2023 at a maximum care University Hospital. 1809 burn injuries were registered in the Emergency Department of the Hospital, including 538 chemical burns to the eye. Deducting the latter of the total number, 24 % affected the hand as an isolated burn and 37 % as a combined burn injury. 43 % of all hand burns (combined and isolated) were female and 57 % were male. The age group from 20 to 29 years was significantly most affected. 21 % of hand burns happened at work, with 80 % of them being male. The most prevalent cause was contact (24 %), at home and at work. 84 % of all hand burns were treated non operatively and did not cause high costs. In general, there has been a decrease of burn injuries worldwide, but we did not recognize a declining trend of hand burns, some of them related to work. Most patients with hand burns present with mild degrees, but particularly work-related hand burns can be more severe with long term sequelae. The study highlights the importance of prevention programs and initiatives.